Technology use of fungi in food and medicinal purposes (Eurasian Journal of Ecology, 2016)
This article discusses the features of fungi in nature and in human economy, commercial cultivation of edible mushrooms. Very large biological and ecological diversity of fungi. Used in the food industry for the preparationof beverages sposobombrozheniya, various fermentation foods. Mushrooms – one of the most important objects of biotechnology applied to the production of antibiotics and other drugs, some chemicals used in the food industry and in technic other hand, fungi can cause considerable damage .
Keywords: mushrooms; aspergillus; plesnevidnye mushrooms; oyster mushroom; gribmaslenok; the concave; fox; morchella; amanita; grebe; kalloriâ; streptomycin; tetracycline; penicillin; giberellin